Age-related sensitive periods influence visual language discrimination in adults - Weikum, Whitney M.; Vouloumanos, Athena; Navarra, Jordi; Soto-Faraco, Salvador; Sebastian-Galles, Nuria; Werker, Janet F. (Frontiers in Systems Neuroscience, 2013)
Adults as well as infants have the capacity to discriminate languages based on visual speech alone. Here, we investigated whether adults’ ability to discriminate languages based on visual speech cues is influenced by the age of language acquisition. Adult participants who had all learned English (as a first or second language) but did not speak French were shown faces of bilingual (French/English) speakers silently reciting sentences in either language. Using only visual speech information, adults who had learned English from birth or as a second language before the age of 6 could discriminate between French and English significantly better than chance. However, adults who had learned English as a second language after age 6 failed to discriminate these two languages, suggesting that early childhood exposure is crucial for using relevant visual speech information to separate languages visually. These findings raise the possibility that lowered sensitivity to non-native visual speech cues may contribute to the difficulties encountered when learning a new language in adulthood.